2019
DOI: 10.1038/s41598-019-45777-w
|View full text |Cite
|
Sign up to set email alerts
|

Methylome and transcriptome maps of human visceral and subcutaneous adipocytes reveal key epigenetic differences at developmental genes

Abstract: Adipocytes support key metabolic and endocrine functions of adipose tissue. Lipid is stored in two major classes of depots, namely visceral adipose (VA) and subcutaneous adipose (SA) depots. Increased visceral adiposity is associated with adverse health outcomes, whereas the impact of SA tissue is relatively metabolically benign. The precise molecular features associated with the functional differences between the adipose depots are still not well understood. Here, we characterised transcriptomes and methylome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
28
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(31 citation statements)
references
References 52 publications
3
28
0
Order By: Relevance
“…Genes related to adipocyte metabolism (proliferation, differentiation, lipid turnover, etc. ), adipokine secretion, and ion channels and cell signaling are also differentially expressed in sWAT and vWAT, according to transcriptome studies [ 34 36 ].…”
Section: Introductionmentioning
confidence: 99%
“…Genes related to adipocyte metabolism (proliferation, differentiation, lipid turnover, etc. ), adipokine secretion, and ion channels and cell signaling are also differentially expressed in sWAT and vWAT, according to transcriptome studies [ 34 36 ].…”
Section: Introductionmentioning
confidence: 99%
“…Although this is the first study to conduct deep proteomic analysis of regional isolated adipocytes, others have previously profiled the transcriptome and proteome of whole VAT and ASAT, which consists of a mix of $50% adipocytes and $50% of other cell types residing in the stromal vascular fraction. Based on the upregulation of inflammatory genes in VAT when compared with ASAT and the upregulation of genes involved in lipid metabolism and insulin signaling in ASAT when compared with VAT, previous transcriptome studies indicate that VAT is associated with cardiovascular diseases and ASAT is associated with improved systemic lipid homeostasis (25)(26)(27). Developmental genes are differentially regulated between ASAT and GFAT (71)(72)(73), and these previous studies highlight that the ASAT gene expression may be similar to VAT.…”
Section: Discussionmentioning
confidence: 97%
“…Another study showed that the proteins involved in cell structure and energy metabolism are differentially expressed between ASAT and GFAT in morbidly obese women (31). Transcriptome analyses of isolated adipocytes are also limited, with differential regulation in genes involved in insulin signaling, lipid metabolism, adipogenic differentiation, angiogenesis, and development reported between adipocytes obtained from VAT and ASAT (25). Another study showed that the transcriptome of adipocytes derived from GFAT is overrepresented with glucose and lipid metabolic pathways compared with adipocytes from ASAT (74).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Metabolically unhealthy obesity is dominated by intra- and extra-abdominal WAT characterized by insulin resistance and inflammation and correlates more to visceral abdominal WAT (vWAT) than to subcutaneous WAT (sWAT) [ 36 ]. According to transcriptome studies, genes associated with adipocyte metabolism, adipokine secretion and cell signaling display a different pattern of expression between sWAT and vWAT [ 40 ], while pathway analysis has shown that genes implicated in inflammation are better expressed in vWAT than sWAT. The reason for these differences has not been fully elucidated but could be partly attributed to the passage of visceral fat products through the portal vein and the resultant drainage into the liver circulation, ultimately leading to systemic metabolic disease and low-grade inflammation [ 36 ].…”
Section: Adipose Tissue Physiologymentioning
confidence: 99%